20-Hydroxyecdysone regulates cytoplasmic actin gene expression in Drosophila cultured cells. - Couderc, J L (1987)
The steroid hormone 20-hydroxyecdysone (20-OHE) induces, in Kc cultured Drosophila melanogaster cells, important morphological transformations and specific changes of enzymatic activities and of protein synthesis. These changes are accompanied by an increase of synthesis and an accumulation of actin. Specific probes were used to reveal transcripts of each actin gene in mRNA populations isolated from cells at various times of 20-OHE treatment. Only the two cytoplasmic actin genes 5C and 42A are expressed in Kc cells and the hormone induces the accumulation of transcripts of these two genes. We have also taken advantage of S1 mapping and extension procedures to identify the 5' ends of the actin mRNAs from these two genes and to compare their respective levels of expression. The 5C gene is more expressed than the 42A one in untreated and in hormone treated cells. The 5C gene encodes three RNAs that differ in their 3' end. The two genes are interrupted by an intervening sequence immediately upstream of ATG initiation codon but not at the same position. The transcription rate for the two genes is increased up to five fold upon 20-OHE treatment, demonstrating a direct effect of the steroid hormone at the transcriptional level for these genes.